2016
DOI: 10.1038/ncomms11519
|View full text |Cite
|
Sign up to set email alerts
|

Giraffe genome sequence reveals clues to its unique morphology and physiology

Abstract: The origins of giraffe's imposing stature and associated cardiovascular adaptations are unknown. Okapi, which lacks these unique features, is giraffe's closest relative and provides a useful comparison, to identify genetic variation underlying giraffe's long neck and cardiovascular system. The genomes of giraffe and okapi were sequenced, and through comparative analyses genes and pathways were identified that exhibit unique genetic changes and likely contribute to giraffe's unique features. Some of these genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 66 publications
4
63
1
1
Order By: Relevance
“…1A). Aside from PRPH2 and CYP27B1 which had previously been shown to be candidates for adaptive evolution in giraffe (Agaba et al, 2016), no additional candidates of positive selection were identified in the giraffe lineages by the present analysis. Substitution analysis shows that the majority of sites (>80%) are conserved between okapi and closely related cetartiodactyl mammals (Fig.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations
“…1A). Aside from PRPH2 and CYP27B1 which had previously been shown to be candidates for adaptive evolution in giraffe (Agaba et al, 2016), no additional candidates of positive selection were identified in the giraffe lineages by the present analysis. Substitution analysis shows that the majority of sites (>80%) are conserved between okapi and closely related cetartiodactyl mammals (Fig.…”
Section: Resultscontrasting
confidence: 48%
“…Variant sites 180 and 233 have Bayes posterior probability of 0.93 and 0.89 respectively. All giraffe’s sequences were found to be identical between NZOO and MA1 (Agaba et al, 2016) verifying that the identified substitutions are not artifacts. (D) The ribbon diagram of giraffe L-opsin highlighting important sequence changes relative to its secondary structure.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…In the giraffe, over half of the genes identified as showing multiple signs of adaption are involved in developmental patterning functional pathways. These include unique changes predicted to be functional in homeobox genes consistent with the growth required to produce and support the long giraffe neck[20]. Killer whale ecotypes show positively selected genes associated with cold adaptation and feeding behavior (mammal or fish predation)[21].…”
Section: Genome Analysis Wish Listsmentioning
confidence: 99%